2021
DOI: 10.3390/biom11121764
|View full text |Cite
|
Sign up to set email alerts
|

Combined Anti-Adipogenic Effects of Hispidulin and p-Synephrine on 3T3-L1 Adipocytes

Abstract: Hispidulin is abundant in Arrabidaea chica, Crossostephium chinense, and Grindelia argentina, among others. p-Synephrine is the main phytochemical constituent of Citrus aurantium. It has been used in combination with various other phytochemicals to determine synergistic effects in studies involving human participants. However, there have been no reports comparing the anti-adipogenic effects of the combination of hispidulin and p-synephrine. The current study explores the anti-adipogenic effects of hispidulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Bitter orange (p-synephrine) has a chemical structure that is similar to ephedrine, and its proposed mechanism of action in humans involves adipogenesis-related protein suppression [CCAAT-enhancer-binding protein α (C/EBPα) and peroxisome proliferator-activated receptor γ (PPARγ)] [ 23 ]. Furthermore, calcium and cAMP signaling pathways and targeting adrenergic receptors [ 24 ] are also related to the anti-adipogenic effect of p-synephrine. Bitter orange extract has been deemed safe for humans to consume both alone and combined with caffeine at rest [ 25 ] as well as during exercise [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bitter orange (p-synephrine) has a chemical structure that is similar to ephedrine, and its proposed mechanism of action in humans involves adipogenesis-related protein suppression [CCAAT-enhancer-binding protein α (C/EBPα) and peroxisome proliferator-activated receptor γ (PPARγ)] [ 23 ]. Furthermore, calcium and cAMP signaling pathways and targeting adrenergic receptors [ 24 ] are also related to the anti-adipogenic effect of p-synephrine. Bitter orange extract has been deemed safe for humans to consume both alone and combined with caffeine at rest [ 25 ] as well as during exercise [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the DPPH radical scavenging activity, the antioxidant values of DDPD, OGPD, CJPD, HYPD, and XYPD were 165.42 ±11. 40 2A). The DDPD and HYPD exhibited the highest DPPH radical scavenging activity but were not significantly different from one another.…”
Section: Antioxidant Activity In Citrus Fruits Extractmentioning
confidence: 98%
“…11 Numerous in vitro and in vivo studies have confirmed the low toxicity and multiple beneficial effects of p-synephrine. [12][13][14][15] In particular, p-synephrine has been popularly used as a dietary supplement to replace ephedrine for weight loss management. 16 However, to the best of our knowledge, few research studies are available describing its hypoglycemic effects.…”
Section: Introductionmentioning
confidence: 99%